UM MÃ‰TODO SIMPLIFICADO PARA OS CÃLCULOS TÃ‰ORICOS DE PRODUÃ‡ÃƒO DE AÃ‡ÃšCAR - Arceneaux, G. (REVISTA DE AGRICULTURA, 2015)
UM MÃ‰TODO SIMPLIFICADO PARA OS CÃLCULOS TÃ‰ORICOS DE PRODUÃ‡ÃƒO DE AÃ‡ÃšCAR